Microplastic Contamination in Coastal Waters of South Larompong, Luwu, South Sulawesi, Indonesia - Widya Ningsih; Khusnul Yaqin; Sri Wahyuni Rahim (Sekolah Tinggi Ilmu Pertanian Wuna, 2022)
Microplastic contamination in the aquatic environment poses a serious threat to the survival of the ecosystem because it is persistent. This study aims to analyze the concentration of microplastics in the water column in the coastal waters of South Larompong. Sampling was carried out using the volume reduce method with the neuston net at four stations, namely Bonepute Beach, Ponnori Beach, Babana Beach and Damaci Beach. The results showed that there was microplastic contamination and found as many as 386 microplastic particles with an average concentration of 2.68 particles/m3. The results of the analysis of microplastic concentrations showed significant differences (P<0.05) between stations. The highest concentrations of microplastics are found on Bonepute Beach which is an area of aquaculture, fishing and densely populated settlements, then followed by Ponnori Beach which is a tourist area. Meanwhile, the lowest microplastic concentrations are found on Babana Beach, which is the estuary area of the Temboe River and Damaci Beach which is a nearby area. Several forms of microplastics were found, namely granules, fibers, films and fragments which were the most dominant forms. Several colors of microplastics were found, namely blue, brown, green, red, white, and black which were the most dominant colors. There are two types of polymer found, namely HDPE (High Density Polyethylene) and PVA (Polyvinyl alcohol). The conclusion of this study is that the coastal waters of South Larompong have been contaminated with microplastics so that more attention is needed regarding the handling of plastic waste, especially microplastics.Â